2020
DOI: 10.1111/tbj.14089
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐based predictive factors of axillary lymph node status in breast cancer

Abstract: Invasive breast carcinoma is the most common malignant neoplasia in women. 1 Beside tumor size, axillary lymph nodes (ALNs) status remains among the most important prognostic factors in terms of breast cancer (BC) survival 2,3 and provides primordial information to guide therapy. Clinical examination, mammography and ultrasonography (US) with image-guided biopsy have been tested for their capacity to predict ALN status. However, the diagnostic accuracy of predicting ALN metastases has not been satisfactory. 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A considerable proportion of patients could be misclassified according to the macro appearance of ALN images, consistent with several previous studies [ 24 , 25 ]. It has been reported that metastatic ALNs accounted for 80.77% of ALNs with short diameters ≥10 mm and 45.28% of ALNs with short diameters of 4–9 mm [ 26 ]. Therefore, traditional imaging tests are of limited value in assessing changes in the tumor microenvironment, especially in predicting ALN status in early BC with no changes in size, morphology, and signal but infiltration of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of patients could be misclassified according to the macro appearance of ALN images, consistent with several previous studies [ 24 , 25 ]. It has been reported that metastatic ALNs accounted for 80.77% of ALNs with short diameters ≥10 mm and 45.28% of ALNs with short diameters of 4–9 mm [ 26 ]. Therefore, traditional imaging tests are of limited value in assessing changes in the tumor microenvironment, especially in predicting ALN status in early BC with no changes in size, morphology, and signal but infiltration of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Color Doppler allows for the visualization of intranodal vascular pattern and the abnormal cortical blood flow to help further increase the detection rates ( 17 ). MRI has a minor role in the diagnosis of breast cancer and metastatic lymph node in a clinical setting, mostly because of its high price and time-consuming features ( 18 , 19 ). According to the literature, the pooled diagnostic sensitivity and specificity of MRI to detect axillary lymph node metastasis in patients with breast cancer were 75%-80% and 89%-91% respectively ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 However, in recent studies, there are conflicting data on ADC value in ALN status. Atallah et al 26 revealed that in breast cancer patients, the difference in ADC values between ipsilateral and contralateral lymph nodes is not significantly associated with ALN positivity and Ramírez-Galván et al 27 stated that the ADC value of metastatic ALN was significantly higher than non-metastatic ALN in 44 cases. In line with the previous meta-analysis study, our study showed that metastatic ALN had lower mean ADC values than non-metastatic ALN and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 99%